Unusual microscopic appearance of Sarcoptes scabiei from skin scrapping sample and its epidemiology - Siagian, Forman E.; ., Ronny; Susiantoro, Urip; Widiyani, Syahfori; Yulia, Hana C.; ., Sisirawaty (International Journal of Research in Dermatology, 2020)
Scabies is still a global parasitic problem with an iceberg phenomenon. Vulnerable people including those with comorbidities and live in close contact to each other in a long time. Its causative agent is Sarcoptes scabiei, an Arthropod which live in the host by burrowing and making tunnel in the skin. The patient usually complaint suffer from nocturnal itching, beside the skin derangement of the affected areas. Here we reported an unusual appearance of S. scabiei from a skin scrapping sample sent to the laboratory of parasitology, Faculty of Medicine, Universitas Kristen Indonesia, Jakarta Indonesia and also discuss its epidemiology.